Technology Based Islamic Curriculum Innovation at SMAIT Nurul Fajri - M. Shalahuddin; Tansah, Lala; Rulia, Rulia; Kurniasih, Nia; Supiana, Supiana; Zaqiah, Qiqi Yuliati (Journal Corner of Education, Linguistics, and Literature, 2025)
Technology-based Islamic curriculum reform is a long-term project that needs to be managed through a detailed strategy. To create this strategy, the management team must analyze the current situation by conducting a thorough environmental scan and by identifying gaps between the current state and the desired program. To be implemented, this new program vision will need to rely on creating several potential ways to produce optimal solutions, which may involve some form of innovation. It is true, to generate the most promising ideas, an environment conducive to reflection and experimentation is needed. Throughout the analysis, decision-making and implementation phases, specific activities need to be organized to involve school members. Additionally, these high-impact projects need to include a parallel change management strategy to account for expected human resistance, both individual and collective (internal culture). This article proposes methods and some concrete actions to help leaders and managers support the development and implementation of new and innovative curricula to promote and support the advancement of local professional practice.